1993
DOI: 10.1152/jappl.1993.74.4.1521
|View full text |Cite
|
Sign up to set email alerts
|

Postburn gastrointestinal vasoconstriction increases bacterial and endotoxin translocation

Abstract: Splanchnic ischemia has been associated with bacterial translocation and increased endotoxin absorption from the gut. To study the effects of major burn on splanchnic circulation, minipigs were randomized to receive 40% flame burn and Parkland resuscitation or sham burn and maintenance fluids. Total and fractionated blood flow, O2 delivery and consumption, mucosal pH of the intestine, and endotoxin levels in the superior mesenteric vein were measured for 48 h, and then abdominal organs were harvested for bacte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
45
0
1

Year Published

1996
1996
2005
2005

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(46 citation statements)
references
References 0 publications
0
45
0
1
Order By: Relevance
“…Both the ileum and colon contain large numbers of gram-negative organisms at higher densities than other body sites, including the skin and oropharynx. Bacterial translocation to extraintestinal sites (such as the mesenteric lymph nodes, spleen, and liver) can occur after burn injury (8,29,57). Furthermore, other shock states, such as hemorrhagic shock, can also lead to endotoxemia, bacterial translocation (3,20,45,46), and myocardial dysfunction (5,14,51).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both the ileum and colon contain large numbers of gram-negative organisms at higher densities than other body sites, including the skin and oropharynx. Bacterial translocation to extraintestinal sites (such as the mesenteric lymph nodes, spleen, and liver) can occur after burn injury (8,29,57). Furthermore, other shock states, such as hemorrhagic shock, can also lead to endotoxemia, bacterial translocation (3,20,45,46), and myocardial dysfunction (5,14,51).…”
Section: Discussionmentioning
confidence: 99%
“…Many of these studies, however, have been complicated by the inability to document endotoxemia consistently after burn injury. Endotoxin has been detected in the first hour after burn injury in both patients (11,60,62) and experimental animals (8,57,67). In general, postburn endotoxemia has been seen after large burns accompanied by inadequate fluid resuscitation or in a burn injury model, with aggressive fluid resuscitation, complicated by sepsis (49).…”
mentioning
confidence: 99%
“…This results in tissue hypoperfusion, leading to hypoxic conditions. Studies have shown that hepatocellular, intestinal, and renal dysfunctions occur early after burn, trauma, and hemorrhagic shock and that these dysfunctions are associated with tissue hypoperfusion (1,16,20,30,33,34). Similarly, alcohol ingestion has also been shown to influence hemodynamic responses (9,11,12,22,28).…”
mentioning
confidence: 99%
“…This concept is supported by data from animal studies in experimental models, including surgical trauma, 2 malnutrition, 3,4 jaundice, 5 pancreatitis, 6 -8 hemorrhagic shock, 9,10 and thermal injury. [11][12][13] These studies have demonstrated the presence of bacterial translocation as measured by the recovery of viable enteric organisms from regional lymph nodes, liver, and other organs, increased intestinal permeability to macromolecules, and systemic endotoxemia.…”
mentioning
confidence: 99%